Enhancement of adhesion between inorganic nanoparticles and polymeric matrix in nanocomposite by introducing polymeric thin film onto nanoparticles. Issue 8 (31st October 2014) - Cha, Sang‐Ho; Bae, Joonwon; Lee, Kyung Jin
<x xml:space="preserve">Abstract</x> Herein, we demonstrate an efficient pathway to improve both affinity and adhesion at interfaces between inorganic nanoparticles and organic polymer matrix by vapor phase incorporation of organic thin layers. The polymeric thin films with an average thickness of a few ∼tens of nanometers were introduced onto the surface of inorganic nanoparticle by vapor deposition polymerization method. Diverse polymers such as vinyl polymers and conducting polymers can be coated on the surface of indium tin oxide (ITO) nanoparticles with a relatively simple method. The polymer‐coated ITO nanoparticles showed improved‐compatibility with polymer matrix in nanocomposite owing to the improved adhesion because of the presence of intermediate polymeric layer. POLYM. ENG. SCI., 55:1906–1911, 2015. © 2014 Society of Plastics Engineers